Paradox of ‘Work from Home’ in Institutions of Higher Learning: The ‘APA’ (Atrophy Performance Assessment) Perspective - Hock, Oo Yu; Sulochana, Nair; Joseph, Adaikalam (2021)
This paper offers two capsulated acronym-approach to understanding the new normal phenomenon of “Work from Home” (WFH) during the blanketed prohibitions of COVID-19 pandemic in institutions of higher learning, particularly private ones, in Malaysia. It does not neglect, however, public ones where similar WFH prohibitive circumstances and inhibitive restrictions stifle the full and vibrant articulations of expressive and interactive face-to-face academic engagements, formal or otherwise within and outside the campuses. In this context, therefore, the first acronym ‘PARADOX’ which represents Perspective, Action, Reality, Agenda, Disruption, Omnipresence and Xenophobia is tendered to capture the essential elements-content on how they collectively instigate, intentionally or insinuatingly, a milieu of cynicism among the academic community specifically and the interested public generally about ‘work from home’ and its impact on their lives and livelihood. Circumscribing the ‘PARADOX’ contextual enunciations, is the second acronym ‘APA’ representing Atrophy, Performance and Assessment tendered as a 3-prong evaluation-approach on the impact of confusing Covid-19 sets of ambiguous-solution pronouncement in order to stimulate a recall of Shakespeare’s ‘Comedy of Errors’ without magnifying the subtle cynicism of a cascading public outcry for business-survival and individual-despair assistance. In essence, WFH is a new normal work-culture with limited options to behave otherwise like before COVID-19 lockdowns that must be cultivated based on a stoical but not necessary fatalistic orientation and nurtured with tenacious resolute values that accepts in good faith a propensity to adapt and change as necessary a disrupted before-lifestyle and values that are increasingly depreciated. The new knowledge and experiences, together with the paradoxical insights of caustic criticisms, should now provide emerging platforms on new learning-learnable curricula for education-training providers and purveyors respectively in the institutions of higher learning, both private and public, without the bureaucratic forbearance of Ministry authority. In conclusion, offered as a dualistic combination of an enigma and axiom manifested in the contention of a ‘paradox’ and ‘oxymoron’ dualism about our lives under the restrictive inhibitions of the COVID-19 pandemic and its ravaging mutations of deadly Delta (and probably more hydra species to spawn), the antilogy of this paper rests on a tongue-incheek approach to the lexicon-interpretation application in viewing the analysis of the COVID-WFH relationship at the macro-level and the WFH-IHE (institutions of Learning) oxymoron relationship at the micro-level, without the benefit of any judgmental wisdom. The aetiology discovered but prescriptive solutions are far from permanent resolutions … yet.